INCREASING STUDENTS’ LEARNING INTEREST THROUGH BLENDED LEARNING IN THE EDUCATIONAL PSYCHOLOGY COURSE - Uswatun Hasanah; Luluk Salimah Oktavia; Putri Silaturrahmi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
Education is a development, reinforcement, and improvement attempt at people’s ability and potential through teaching, guidance, example, and so on needed by themselves, other people, and nation and state. In fact, there are many students who believe that learning is not fun so their interest in learning decreases. Therefore, innovative learning is needed to increase students’ interest in learning. One of the attempts is to apply the Blended Learning model. This paper aims to determine whether there is a significant effect of blended learning on students’ learning interest in educational psychology courses. This paper is quantitative research with a causal type, which involved 43 third-semester students of the Islamic Education study program of IDIA Prenduan. Based on the findings of the data analysis tested through simple linear regression, the value of the t-count of 0.847 is smaller than t-table 2.019 at a significant level of 5%. It can be concluded that blended learning has an insignificant effect on students’ learning interest in Educational Psychology courses of the Islamic Education study program of IDIA in the academic year 2021-2022.